ANALISIS FAKTOR YANG MEMPENGARUHI KEPATUHAN MASYARAKAT TERHADAP NORMA KAWASAN BEBAS ASAP ROKOK DI KELURAHAN AGROWISATA - Fajriani Ananda; T. Romi Marnelly; Ice Irawati; Andry Sukarmen; Alkausyari Aziz (Pelantar Press, 2023)
Smoking is one of the negative habits that is quite difficult to change even though its negative effects have often been informed. Cigarette smoke is not only harmful to active smokers but also passive smokers. So the habit of smoking should be stopped. In Pekanbaru city, there is an area that has been officially designated as a smoke-free area, namely RT 05 RW 05 Agrotourism Village, Rumbai District. Although the smoking habit is difficult to change, in this predetermined area there continues to be an increase in the number of respondents who smoke. This study analyzed what factors influenced respondents to stop smoking and comply with the norms of the smoke-free area. This research uses a descriptive quantitative approach. With a population of all residents of RT 05 RW 05 who are categorized as having smoked, there are 24 people who are also used as samples. Sampling is done by census. quantitative processing of data with simple mathematics. The results showed that the factors that influence people's compliance with the norms of smoke-free areas are public knowledge of the norms of smoke-free areas and knowledge of the dangers of cigarettes, involvement in socialization, supervision and situations.